1979
DOI: 10.1289/ehp.7928115
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium effects in rats on tissue iron, selenium, and blood pressure: blood and hair cadmium in some Oregon residents

Abstract: Exposure of rats to cadmium causes a marked depletion of iron in liver and kidney. Selenium neither counteracts or intensifies the influence of cadmium on tissue iron levels. Selenium injections protect against cadmium-induced testicular damage but cause this element to accumulate in the testes at higher concentration than in animals exposed to cadmium without selenium. Selenium injection diverts the binding of cadmium from low molecular weight proteins to high molecular weight ones. Dosing rats with selenium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

1985
1985
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 25 publications
1
11
0
1
Order By: Relevance
“…It is well known that DMT1 protein levels are upregulated in anemic rats (Thompson et al, 2007;Fleming et al, 1998). It has been reported that oral Cd intake reduces hemoglobin concentration of rat and leads to iron-deficiency anemia (Whanger, 1979;Schumann et al, 1996). In this study, hematocrit and hemoglobin were measured to investigate whether Cd administration caused anemia or not.…”
Section: Discussionmentioning
confidence: 96%
“…It is well known that DMT1 protein levels are upregulated in anemic rats (Thompson et al, 2007;Fleming et al, 1998). It has been reported that oral Cd intake reduces hemoglobin concentration of rat and leads to iron-deficiency anemia (Whanger, 1979;Schumann et al, 1996). In this study, hematocrit and hemoglobin were measured to investigate whether Cd administration caused anemia or not.…”
Section: Discussionmentioning
confidence: 96%
“…One o f the wor st problems concerns the measurem ent of cadm ium exposure. Man y studies estimated the exposure by measur ing cadmium in blood (77,80,124,137,138,140,141,(148)(149)(150)(151)153). The blood cadmium level is, however, not a very reliable mea sure of the cadmium body burden.…”
Section: Cadmiummentioning
confidence: 99%
“…It was found, however, that blood pressure was elevated only when Long-Evans strain rats were fed with cadmium mixed with rye [45]. Schroeder et al [46] reported later that the average elevation in blood pressure was 42 mmHg, almost half of that of the former report, in suckling Long-Evans strain rats given drinking water containing 5 ppm of cadmium acetate over a period of 400 days.…”
Section: Negative Datamentioning
confidence: 92%